Assessing recycled pavement concrete mechanical properties under joint action of freezing and fatigue via RSM. (10th March 2018) - Li, Wenzhe; Cai, Liangcai; Wu, Yonggen; Liu, Qingtao; Yu, Hongjiang; Zhang, Chujie
Highlights: The RSM was used to assess the mechanical properties of PRAC under the joint action of freezing and fatigue. The number of fatigue iterations influences flexural strength, while freeze-thaw cycles influence compressive strength. The interaction between fatigue iterations and freeze-thaw cycles substantially impacts the relative dynamic modulus of PRAC. Abstract: Sample pavement recycled aggregate concrete (PRAC) was prepared with waste pavement concrete from an airport in China in this study. Frost resistance and fatigue performance were analyzed by comparison against common pavement concrete. The response surface method (RSM) was used to assess the mechanical properties of PRAC under the joint action of freezing and fatigue. Design Expert and Center Composite Design (CCD) software were applied to analyze the influence rules dominating freeze-thaw cycles, fatigue iterations, and their joint action in regards to the flexural strength, compressive strength, and relative dynamic modulus of PRAC with corresponding RSM models. The three RSM relation models were fit well and effectively represent PRAC characteristics after a series of fatigue and freeze-thaw cycles. The number of fatigue iterations appears to influence flexural strength, while freeze-thaw cycles influence compressive strength; the interaction between fatigue iterations and freeze-thaw cycles substantially impacts the P n of PRAC.